SOCIAL VALUE AS A MARKETING STRATEGY IN A BRAZILIAN CREDIT UNION - Scharf, Edson Roberto; Gehrke, Germano; Sousa, Richard Perassi Luiz de (Perspectivas Contemporâneas, 2016)
The purpose is to examine the strategic Marketing direction of Brazil’s largest credit union adopted in order to enhance the social value of its brand. For this, a qualitative exploratory research, carried out by a triangulation of data from three in-depth interviews within a central credit union and an official published document was made. It is a single case study, with an expository rating, according to Yin (2003). The results indicated that engaging and relationship building actions can be efficient tools for the dissemination of cooperative principles and can be achieved at a lower cost than traditional banking marketing tools. This is the first study exploring the social value theme as a marketing strategy within credit unions in Brazil. RESUMO O objetivo é examinar o direcionamento estratégico de Marketing da maior cooperativa de crédito do Brasil adotado para incrementar o valor social de sua marca. Para tanto, utilizou-se de uma pesquisa exploratória qualitativa, composta de três entrevistas em profundidade em uma central de cooperativas de crédito e documento oficial publicado, para triangulação de dados. É um estudo de caso único, com classificação expositiva, de acordo com Yin (2003). Os resultados indicaram que o envolvimento e as ações de construção de relacionamento podem ser ferramentas eficientes para a difusão de princípios cooperativos e pode ser alcançado a um custo menor do que ferramentas de Marketing bancário tradicional. Este é o primeiro estudo a explorar o tema valor social como estratégia de Marketing dentro de cooperativas de crédito no Brasil.